PENGUJIAN BEBERAPA PESTISIDA NABATI UNTUK PENGENDALIAN SERANGAN HAMA ULAT API PADA DAUN TANAMAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) DI DESA TOMUAN HOLBUNG KECAMATAN BANDAR PASIR MANDOGE - Muhammad Taufiq (JASA PADI, 2020)
The decline in the production of oil palm yields in Tomuan Holbung Village,Bandar Pasir Mandoge Subdistrict, Asahan District was identified as a result of a very highlevel of pest infestation. Pests that are often found and becomes the problems are Setothoseaasigna larva. Controlling these pests is a relatively high cost through the application ofchemical synthetic pesticides. The purpose of this research to determine the best formulationof botanical pesticides and their influence in reducing Setothosea asigna larva pests.Botanical pesticides which will be tested in this research are based from garlic, lemongrassleaves, pepper seeds, turmeric, tobacco leaves and papaya leaves. Formulations from eachsource of vegetable material were put into the leaves of palm plants and then tested onSetothosea asigna larva. The parameter observed in this study was the level of palatability ofSetothosea asigna larva. The observations made were based on the level of decrease in thepercentage of feeding activity, the weight of feed (palm oil plant leaves) that were consumedby the Setothosea asigna larva in the period 1-6 days after application. The results of thestudy showed that all treatments of botanical pesticides consisting of: 1) garlic, 2) lemongrass leaves, 3) pepper seeds, 4) turmeric tubers, and 5) tobacco leaves were significantlydifferent from without treatment or control. Then the results of the study also showed that theapplication of botanical pesticides affected the palatability of the Setothosea asigna larva,which accelerated death, appetite and decreased eating activities. The best treatment ofvegetable pesticides from tobacco leaves in controlling the Setothosea asigna larva'spalatability. Setothosea asigna larva die on first day, It don’t want to eat after the applicationof botanical pesticides, and the level of eating activity decreases to 100%.Keywords : Setothosea asigna larva, botanical pesticide, palm plants